Revision of the sweetpotato segmentation and estimation of segments’ size: Are we missing some major opportunities for more-targeted breeding? - Naziri, Diego; Saali, Reuben (International Potato Center, 2024)
Following a consultative process by Market Intelligence, the International Potato Center (CIP), and NARES an opportunity was identified to expand and refine the initial seed product market segmentation for sweetpotato. In particular, the market segmentation effort by the Excellence in Breeding (EiB) and Market Intelligence initiatives had initially focused on identifying market segments aligned to existing breeding pipelines, or in other words, segments which CGIAR centers are already breeding for. Due to the limited resources, this was already a major step ahead to support the decision making on investment allocations across different pipelines. However, this could not answer the question whether alternative investments should be considered. In 2023, several segments not aligned to CIP breeding pipelines were identified. These included both segments in CGIAR sub-region regions which were already included in the initial EiB segmentation and segments in sub-regions which were completely omitted in it. Overall, this exercise resulted in a significant increase in identified market segments for sweetpotato, from 14 to 32. In 2024, an e-survey was launched to elicit expert opinions about the crop acreage aligned to each of these segments. This has allowed to identify large market segments that have not been yet targeted and offer opportunities for enhancing the impact of the breeding effort by CIP and partners.